Disease hotspots or hot species? Infection dynamics in multi‐host metacommunities controlled by species identity, not source location. (1st May 2020) - Wilber, Mark Q.; Johnson, Pieter T. J.; Briggs, Cheryl J.
Abstract: Pathogen persistence in host communities is influenced by processes operating at the individual host to landscape‐level scale, but isolating the relative contributions of these processes is challenging. We developed theory to partition the influence of host species, habitat patches and landscape connectivity on pathogen persistence within metacommunities of hosts and pathogens. We used this framework to quantify the contributions of host species composition and habitat patch identity on the persistence of an amphibian pathogen across the landscape. By sampling over 11 000 hosts of six amphibian species, we found that a single host species could maintain the pathogen in 91% of observed metacommunities. Moreover, this dominant maintenance species contributed, on average, twice as much to landscape‐level pathogen persistence compared to the most influential source patch in a metacommunity. Our analysis demonstrates substantial inequality in how species and patches contribute to pathogen persistence, with important implications for targeted disease management. Abstract : Pathogen persistence in host communities is influenced by processes operating at the individual host to landscape‐level scale, but isolating the relative contributions of these processes is challenging. We developed and applied theory to partition the influence of host species, habitat patches, and landscape connectivity on pathogen persistence within metacommunities of hosts and pathogens. Our analysis demonstrates substantial inequality in how species and patches contribute to pathogen persistence, with important implications for targeted disease management.